Test time augmentation by regular shifting for deep denoising autoencoder networks - Rodriguez-Rodriguez, Jose A.; Molina-Cabello, Miguel A.; Benitez-Rochel, Rafaela; Lopez-Rubio, Ezequiel (Proceedings of ... International Joint Conference on Neural Networks, 2021)
Image restoration, which is the process of denoising noisy images in order to recover their latent clean images, has been frequently addressed. The importance of this field resides in the impact of noisy images on the performance of computer vision systems. In this work, a deep autoencoder neural network architecture is proposed to denoise images affected by Gaussian noise. The performance of the system is enhanced by using a test time augmentation scheme. Experiments have been carried out by considering different levels of Gaussian noise. Results demonstrate the suitability of the proposed methodology in order to enhance the quality of the image restoration process in images affected by Gaussian noise.